Leeuwenhoek's Legatees and Beijerinck's Beneficiaries : A History of Medical Virology in The Netherlands - Doornum, Gerard van; Sankaran, Neeraja (Book collections on Project MUSE., 2020)
This book offers a tour of the history of medical virology in the Netherlands from the nineteenth century to the new millennium. Beginning with the discovery of the first virus by Martinus Beijerinck in 1898, the authors investigate the reception and redefinition of his concept in medical circles and its implications for medical practice, particularly in the diagnosis and prevention of viral infections. The relatively slow progress of these areas in the first half of the twentieth century and their explosive growth in the wake of molecular techniques are examined. The surveillance and control of virus diseases in the field of public health is treated in depth, as are tumour virus research and the important Dutch contributions to technical developments instrumental in advancing virology worldwide. Particular attention is paid to oft forgotten virus research in the former Dutch colonies in the East and West Indies and Africa.